Breaking the cycle: A comparison between intravenous immunoglobulins and high dosage prednisone in the treatment of medically intractable epilepsy in children. (April 2017) - Tang-Wai, Richard; Mailo, Janette; Rosenblatt, Bernard
Highlights: A comparison between IVIg and prednisone in treating pediatric refractory epilepsy. The IVIG cohort had greater seizure reduction and lower adverse effects. Response was independent of epilepsy type, etiology, and duration of epilepsy. A common immune-mediated pathway to medical intractability is suggested. Abstract: Purpose: Because immune mediated mechanisms are suspected in epileptogenesis, IVIg and corticosteroids have been used as alternatives to treat refractory seizures. We present our experience treating intractable epileptic children with IVIg and prednisone. Methods: Children with intractable epilepsy treated with prednisone or IVIg between 2005–2016 were reviewed retrospectively. Children with infantile spasms and autoimmune epilepsy were excluded. Data analyzed include epilepsy type and etiology, duration of epilepsy prior to treatment, seizure outcome, time to best seizure outcome, and adverse effects. Results: Fifty-one patients were included: 26 received IVIg; 25 received prednisone. Etiologies were similar between cohorts: genetic (13 IVIg; 10 prednisone), lesional (8 IVIg; 7 prednisone), and unknown (5 IVIg; 8 prednisone). In the prednisone cohort, 92.0% had generalized epilepsy compared to 61.5% for IVIg. Among the IVIg treated, 84.6% responded (10 genetic, 4 unknown, and 8 lesional) with mean seizure reduction of 77.3% and mean time to best response of 9.8 weeks. With prednisone, 24.0% responded (2 genetic, 3 unknown, and 1 lesional) with a mean seizure reduction of 95.0% and mean time to best response of 2.7 weeks. Adverse effects occurred in 2 and 16 patients treated with IVIg and prednisone, respectively. The difference in responders and seizure reduction was statistically significant (p < 0.0001 and p = 0.001, respectively). Conclusion: IVIg had greater responders and lower adverse effects and honeymoon effect. This response was independent of epilepsy type, etiology, and duration suggesting different mechanisms of action between prednisone and IVIg and a common, reversible, immune-mediated pathway to intractability.